Mariculture is a double-edged sword in China. (30th June 2019) - Meng, Weiqing; Feagin, Rusty A.
Abstract: China now accounts for over 2/3 of the world's production of marine-based seafood. Chinese mariculture has contributed to the stability of the global food supply, but millions of tons of excess feed and drugs are threatening the sustainability of the waters in which it is conducted. Over 26% of the excess nitrogen in China's waters is likely a result of shrimp production alone, worsening eutrophication and the resulting 'red tide' in China. While some Chinese operations require the destruction of carbon-rich wetlands, the sector as a whole can be considered a net CO2 sink at the immediate time of harvest; each year, Chinese mariculture extracts the same quantity of CO2 from the atmosphere as 5000 km 2 of forest. Novel technical practices, improved management of the harvested products in the food versus industrial supply chain, optimized sea-use and land-use plans, and the encouragement of participatory decision-making by provincial entities offer some promise to ensure the sustainability of this global public resource – but the national Chinese government will have to step up to address the challenges.